Immunocytochemical investigation of immune cells within human primary and permanent tooth pulp - H. D. RODD, & F. M. BOISSONADE (IAPD and Blackwell, 2006)
Aim.The aim of this study was to determine whether there are any differences in the number and distribution of immune cells within human primary and permanent tooth pulp, both in health and disease.